Financialisation, debt and inequality: Scenarios based on a stock flow consistent model - Daniel Detzer (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2016)
In the era of financialisation, increasing income inequality could be observed in most developed and many developing countries. Despite these similar developments in inequality, the growth performance and drivers for growth differed markedly among countries, allowing clusters of different growth regimes to be identified. Among them two extreme types: the debt-led private-demand boom type and the export-led mercantilist type. Whereas the former relies mainly on creditfinanced household consumption in order to compensate for the potential lack of demand (associated with the depressing effect of financialisation), the latter relies on net exports as the main driver of aggregate demand. After a short review of the different channels through which financialisation is expected to affect a countries development, a theoretical discussion on the conditions that tend to support the occurrence of either of the two regimes will build the base for the following model exercise. With the help of a stock-flow consistent model it will be demonstrated then how increasing inequality, depending on a countries institutional structure and regulatory framework, affects growth differently, explaining the occurrence of both regime types. Based on the insights of the theoretical discussion and the model results, a foresight exercise will be performed examining how further increase in inequality might affect development of economies around the world but particularly of the Euro area.
Keywords: E02; E12; E21; E25; E44; E65; F40; F41; F43; 330; Euro area; finance-dominate capitalism; financialisation; foresight; household debt; international imbalances; consumption emulation